The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.17235/reed.2015.3953/2015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a gluten-free diet on bone mineral density in celiac patients

Abstract: Background: Osteoporosis (OP) is a metabolic bone illness that may complicate celiac disease (CD). It can lead to devastating consequences because of low bone mass and fragility fractures.Purpose: To study the OP prevalence in a group of Brazilian patients with CD and the value of a gluten free diet (GFD).Methods: Retrospective study of celiac female patients from a single University Center followed with bone densitometries. Results from densitometry made at first visit were compared with a second study after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Other complications related to CD involve bone health, which is closely related to the nutritional status especially of calcium and vitamin D [75]. Impaired bone health is highly prevalent in children and adults at diagnosis of CD, even in individuals with mild enteropathy (without villous atrophy) [43,44,[76][77][78][79][80][81][82][83][84][85]. In adult onset CD, a GFD generally improves but rarely normalizes BMD and the serious impact of this is shown in studies examining fracture risk [51,86].…”
Section: Comorbidities Potentially Related To Nutrient Deficiencies Imentioning
confidence: 99%
“…Other complications related to CD involve bone health, which is closely related to the nutritional status especially of calcium and vitamin D [75]. Impaired bone health is highly prevalent in children and adults at diagnosis of CD, even in individuals with mild enteropathy (without villous atrophy) [43,44,[76][77][78][79][80][81][82][83][84][85]. In adult onset CD, a GFD generally improves but rarely normalizes BMD and the serious impact of this is shown in studies examining fracture risk [51,86].…”
Section: Comorbidities Potentially Related To Nutrient Deficiencies Imentioning
confidence: 99%
“…Celiac disease (CD) is a chronic enteropathy, characterized by permanent gluten intolerance in genetically predisposed people (1,2) . The disease affects about 1% of the world's population with a predominance of young adults (3,4) .…”
Section: Introductionmentioning
confidence: 99%
“…3 It has been demonstrated that up to 75% of patients with coeliac disease (CD) suffer from bone mass loss (osteopenia or osteoporosis). [4][5][6][7][8][9][10] Despite the strong association between low BMD and CD, guidelines do not express with certainty whether each patient with a new diagnosis of CD should undergo a DEXA scan. [11][12][13] At present, DEXA investigations are suggested only for patients with CD who are peri-or post-menopausal females or males over 55 years and those with overt malabsorption or a history of fragility fractures.…”
Section: Introductionmentioning
confidence: 99%